Evaluation of plastic collapse load factor value of two span steel beams under concentrated loads by fuzzy logic - Tanyildizi, Harun; Yazicio?lu, Salih (My University, 2006)
In this study, collapse load factor value for plastic collapse of steel beams has been found by fuzzy logic approach. A fuzzy logic control system was simulated by the software SIMULINK. MATLAB was used for its mathematical calculations. A fuzzy logic controller is also placed with in a SIMULINK model. The membership functions were chosen by the experiences gained, and their base values were selected by concentrating on more sensitive regions. Rule base was constituted by an expert experience and the obtained results were compared with the ones calculated by the classical methods and found remarkably close to each other.
Bulanik mantik metodu ile tekil yükler altinda i?ki açiklikli kirişlerin plastik göçme yük faktörü de?erinin bulunmasi
Keywords: Collapse Load Factor; Fuzzy Logic Controller; Plastic Analysis